Analysis of 21st-century skills through science literacy in fifth grade science teaching at SDN Lebbek 1 - A’as Maghfiroh; Viza Maharani; Agung Setyawan (Educenter : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this research to obtain information on the extent to which 21st century skills are improved through scientific literacy. The problem in this research is "is there an increase in the scientific literacy ability of fifth grade students in science learning at SDN LEBBEK 1". The subjects in this study were teachers and students of class V SDN LEBBEK 1 for the academic year 2022/2023 which collected 17 students, consisting of 6 male students and 11 female students. The data collection techniques used in this study were observation, interviews and questionnaires.The data analysis technique used is quantitative technical, quantitative technique to process quantitative data from test results. The instruments used are student and teacher activity observation sheets, interview question sheets and questionnaires for students.